A Real-Life Study on the Use of Tildrakizumab in Psoriatic Patients - Elena Campione; Sara Lambiase; Ruslana Gaeta Shumak; Marco Galluzzo; Caterina Lanna; Gaetana Costanza; Cristiana Borselli; Fabio Artosi; Terenzio Cosio; Lorenzo Tofani; Annunziata Dattola; Francesca Di Daniele; et al. (MDPI AG, 2023)
Tildrakizumab is a humanized IgG1κ monoclonal antibody that selectively targets the p19 subunit of interleukin IL-23, thereby inhibiting the IL-23/IL-17 axis, which is primarily implicated in the immunopathogenesis of psoriasis. Tildrakizumab is approved for the treatment of moderate-to-severe plaque-type psoriasis in adults based on the evidence of two randomized and controlled phase-III clinical trials (reSURFACE 1 and reSURFACE 2). Here, we report our real-life experience treating 53 psoriatic patients (19 female and 34 male) who were administered tildrakizumab every 12 weeks and received follow-ups over 52 weeks. Descriptive and inferential statistical analyses were performed, in particular the Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI) and, if applicable, the Nail Psoriasis Severity Index (NAPSI) and Palmoplantar Psoriasis Physician Global Assessment (PPPGA). These were assessed at baseline and after different timepoints (weeks) during the follow-up period. We described and evaluated demographical and epidemiological characteristics in our cohort group, focusing on comorbidities. In this group, 35.9% of patients were female and 64.1% were male, with 47.1% being smokers and with a mean age of 51.2 years. A total of 37.7% of these patients was affected by scalp psoriasis; regarding comorbidities, hypertension was the most frequent (32.5%), followed by psoriatic arthritis (PsA) (18.60%) and diabetes (13.9%). At week 52, 93%, 90.2% and 77% of patients achieved a PASI reduction ≥75% (PASI 75), PASI 90 and PASI 100, respectively. In addition, NAPSI, PPPGA and DLQI scores were significantly reduced by week 52. In our cohort of complex psoriasis patients, disease remission began at the end of the fourth week of treatment and remained constant from week 16 to week 52.